2017
DOI: 10.1038/s41467-017-00750-x
|View full text |Cite
|
Sign up to set email alerts
|

MANF regulates hypothalamic control of food intake and body weight

Abstract: The hypothalamus has a vital role in controlling food intake and energy homeostasis; its activity is modulated by neuropeptides and endocrine factors. Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a neurotrophic factor that is also localized in the endoplasmic reticulum (ER) in neurons. Here we show that MANF is highly enriched in distinct nuclei of the mouse hypothalamus, and that MANF expression in the hypothalamus is upregulated in response to fasting. Increasing or decreasing hypothalamic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 61 publications
(71 reference statements)
6
47
4
Order By: Relevance
“…On the contrary, Manf fl/fl ::Nestin Cre/1 mice are viable and have a normal lifespan without diabetes or gross defects, but adult Manf fl/fl ::Nestin Cre/1 mice have a decreased body weight when compared with littermate Manf fl/fl controls. In a recent study, Manf knock-down by siRNA from the hypothalamus resulted in hypophagia and reduced body weight (Yang et al, 2017), suggesting that Manf fl/fl :: Nestin Cre/1 mice could be smaller due to hypophagia. However, Nestin Cre/1 mice themselves have been reported with a growth defect due to reduced levels of mouse growth hormone (Galichet et al, 2010;Declercq et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, Manf fl/fl ::Nestin Cre/1 mice are viable and have a normal lifespan without diabetes or gross defects, but adult Manf fl/fl ::Nestin Cre/1 mice have a decreased body weight when compared with littermate Manf fl/fl controls. In a recent study, Manf knock-down by siRNA from the hypothalamus resulted in hypophagia and reduced body weight (Yang et al, 2017), suggesting that Manf fl/fl :: Nestin Cre/1 mice could be smaller due to hypophagia. However, Nestin Cre/1 mice themselves have been reported with a growth defect due to reduced levels of mouse growth hormone (Galichet et al, 2010;Declercq et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, decreased MANF expression in the hypothalamus results in hypophagia and reduced body weight. Increased MANF at the ER has been suggested to recruit and activate PIP4k2b, thus reducing AKT phosphorylation downstream of insulin receptor signaling leading to the hyperphagia (66). This result suggests that cellular MANF levels are critical for insulin-regulated AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, addition of MANF to ER-stressed b-cells might reduce ER stress and lead to increased b-cell proliferation. A recent study revealed that genetically induced MANF overexpression in the hypothalamus leads to increased feeding behavior and obesity in mice caused by impaired insulin signaling and insulin resistance in the hypothalamus (66). In contrast, decreased MANF expression in the hypothalamus results in hypophagia and reduced body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Factors cause excessive accumulation of unfolded or misfolded proteins in the ER, triggering ER stress (ERS) [8]. Studies in mice revealed that MANF overexpression in hypothalamus caused insulin resistance [9], while systemic overexpression of MANF markedly improved glucose and insulin tolerance [10]. In humans, circulating MANF was found to be positively correlated with insulin resistance in patients with prediabetes, but was unrelated to insulin resistance in patients with T2DM [11].…”
Section: Introductionmentioning
confidence: 99%